Exploring Student’s Learning Enjoyment and Vocabulary Mastery in Digital Game-Based Learning Experience: A Narrative Inquiry - Anisa Pratiwi; Nur Arifah Drajati; Ellisa Indriyani Putri Handayani (EDULANGUE, 2022)
Digital Game-Based Learning has gained numerous attentions among researchers and educators for its fun-learning concept that promotes learners’ enjoyment. The present study explicates two things: the learning enjoyment reported by EFL learners based on Fu et al., (2009) ’s EGameFlow and the impacts on EFL learners’ vocabulary mastery based on Nation’s (2001) concept, while playing games. This study involved an Indonesian EFL learner who is also an active digital game player. Narrative Inquiry methods were applied to present the findings. Thus, observations, learner’s reflection diary, interviews, and artifacts are involved in the data analysis. The results showed that 6 out of 8 dimensions of EGameFlow emerged, and vocabulary mastery was achieved through Nation’s (2001) concept—along with 78 new words and phrases learned. Furthermore, by looking deep into the participant’s stories, the findings also generate meaningful implications for vocabulary learning and learning enjoyment in digital game-based learning.